A US national update of health condition prevalence among privately-insured autistic adults - Anne Longo; Deondray Radford; Brittany N Hand (Becaris Publishing Limited, 2024)
Aim: Previous research using state or regional samples has shown that autistic adults have a higher prevalence of health conditions in comparison to the general population. Methods: To build upon this important previous research, we conducted a cross-sectional retrospective study of 2019-2020 healthcare claims to determine the prevalence of conditions in a US national sample of privately insured autistic adults (n = 30,258) and an age- and sex-matched population comparison (n = 60,516) group of adults without autism diagnoses. Results: Like previous studies, we found that autistic adults had significantly greater odds of most mental and physical health conditions. However, our prevalence estimates differed from previous studies for several mental and physical health conditions. For example, our sample of autistic adults had higher prevalence of anxiety disorders (55%) and attention deficit hyperactivity disorders (34%), but lower prevalence of asthma (9%) and sleep disorders (3%) than previous studies. Discussion & conclusion: Our use of a large US national sample, more recent healthcare claims data, and different methods for identifying health conditions may have contributed to these differences. Our findings alert healthcare providers and policymakers to the health conditions most common among the growing population of autistic adults. We hope these findings lead to improved screening and management of these conditions, inform initiatives to improve access to healthcare, and guide future funding.